FACTS allocation considering loads uncertainty, steady state operation constraints, and dynamic operation constraints - M. M. H. Elroby; S. F. Mekhamer; H. E. A. Talaat; M. A. Moustafa Hassan (International Journal of Electrical and Computer Engineering (IJECE), 2021)
This study proposes an algorithm to allocate different types of flexible AC transmission system (FACTS) in power systems. The main objective of this study is to maximize profit by minimizing the system’s operating cost including FACTS devices (FDs) installation cost. Dynamic and steady state operating restrictions with loads uncertainty are included in the problem formulation. The overall problem is solved using both teaching learning based optimization (TLBO) technique for attaining the optimal allocation of the FDs as main-optimization problem and matpower interior point solver (MIPS) for optimal power flow (OPF) as the sub-optimization problem. The validation of the proposed approach is verified by applying it to test system of 59-bus; Simplified 14-Generator model of the South East Australian power system.